Systemic inflammation response index (SIRI)-based risk of pneumonia following successful PCI in STEMI patients - Dan Yan; Saibin Wang (Annals of Medicine)
Background In patients with ST-elevation myocardial infarction (STEMI), pulmonary infection after successful primary percutaneous coronary intervention (PCI) is a severe complication that often results in death. It is not known whether there are any predictive markers for the onset of pneumonia in STEMI patients after successful PCI.Methods According to whether pneumonia occurred within two weeks of PCI, 619 STEMI patients were divided into pneumonia and nonpneumonia groups. The area under the receiver operating characteristic curve (AUC) was used to assess the predictive accuracy of the SIRI for pneumonia risk following successful PCI. Using a restricted cubic spline (RCS) and multivariate regression analysis, we investigated the relationship between the SIRI and PCI-induced pneumonia.Results Patients in the pneumonia group had a significantly greater SIRI than did those in the nonpneumonia group at admission (7.81 ± 7.53 vs. 3.35 ± 3.08, p < 0.001). Patients in the SIRI ≥ 4.04 group exhibited greater vulnerability to pneumonia after successful PCI than did those in the SIRI < 4.04 group (OR: 5.20, 95% CI: 3.53–7.72, p < 0.001). According to the ROC curve, the SIRI is highly predictive of pneumonia after PCI for STEMI patients, with an AUC of 0.766 (95% CI: 0.724–0.808). As the SIRI increased, the pneumonia risk increased in the RCS model.Conclusion As a result of PCI for STEMI patients, the SIRI is a good indicator of pneumonia risk. The likelihood of pneumonia occurring in STEMI patients after PCI generally increases with increasing SIRI.